Analysis of The Influence Auto Gate System and Terminal Booking System on Customer Satisfaction PT. JICT - Denny J. Najoan; Alfais Amin Darmawan; Ahmad Zaki Hidayawan; Riqqah Nabilah (Jurnal Ilmu Multidisiplin, 2025)
PT. JICT is one of the operators in the terminal part of PT Subholding PT. Pelindo terminal container. The purepose of this study was to analyze the effect oh the Auto Gate System ( AGS ) and Terminal Booking System ( TBS ) on customer satisfaction. This research uses quantitative methods. The sampling technique used was saturated sampling with 30 respondents and the data was processed using SPSS version 26. The data was analyzed by validity test, reability test, multiple regression analysis, determination coefficient test (R2), T test, and F test. Based on the result of the analysis and discussion the test shows that the F-count > F-table which atates that AGS and TBS have a positive and significant effect on customer satisfaction at PT. JICT. The F test shows that the F-count> F-table partially AGS and TBS have a positive and significant effect on customer satisfaction at PT. JICT. PT JICT has supporting facilities to meet the needs of service users so that the services provided are as expected. This company provides services for loading and unloading export and import containers from and to ships, providing temporary stacking services for export and import containers, providing reefer services and providing Gate services. Loading and unloading of export containers is the most frequently served activity in this company, the development of technology from year to year, the development of services must also be further developed, so this company tries to provide facilities and equipment in accordance with developments and technology so as not to be left behind so that service users will be more interested in choosing PT JICT services. Apart from facilities and equipment, this company also has reliable human resources and high integrity. After the facilities and equipment are available, it is necessary to provide good service starting from the entry of goods into PT JICT through the Gate using a new system, namely the JICT Auto Gate System (JAGS).(Immanuel, 2015)